Analisis Faktor-Faktor yang Memengaruhi Source of Consumer Information pada Pengunjung UKM Agrowisata - Vicka Pramudya Putra; John Nefri; Roni Afrizal; Indria Ukrita; Arnayulis; Azzukhruf Ariliusra (Journal of Trends Economics and Accounting Research, 2023)
Technological developments play an important role in marketing activities, one of which is digital marketing through social media. With the existence of social media, it becomes easier, faster and lower cost for consumers to obtain information related to products or services offered by business organizations such as Small and Medium Enterprises. However, information on social media is less trustworthy and less credible because of several biases, so many consumers still rely on word of mouth when they want to search for or dig up information about products or services. The use of appropriate information sources has an influence on marketing strategies in business organizations such as Agrotourism SMEs, one of which is Dangau Abak. The lack of marketing research in Agrotourism SMEs, especially in the field of prepurchasing, is one of the reasons why this research is important to carry out. This research aims to determine the source of consumer information used by visitors to obtain information (word of mouth or social media) and analyze the factors that influence the use of this information source. This research was conducted on visitors to the Dangau Abak Agrotourism UKM which is a Small and Medium Enterprise in the Agrotourism sector with a total of 65 visitors as respondents. Data analysts use a binary logistic regression model with data collection techniques using observation, interviews and questionnaires. This research shows that most visitors obtain information about Dangau Abak Agrotourism UKM from social media, namely 57%. This research concludes that age and interaction with social media influence the use of information sources, both word of mouth and social media.